US government natural disaster assistance: historical analysis and a proposal for the future - Barnett, Barry J. (1999)
Governments often provide grants or low-interest loans to disaster victims. Yet these programames have proven to be quite costly. In addition, questions have been raised about associated behavioural incentives. Conceptually, government disaster insurance programmes should be more efficient, consistent and equitable than ex post facto disaster relief in the form of grants and loans. Yet the performance of government disaster insurance programmes has been mixed, at best. This article reviews the history of US federal natural disaster assistance to individuals and concludes with a recommendation for a new government role in the provision of disaster insurance. - Reproduced
Keywords: Disaster relief - United States; Disaster relief